Analysis of Idiom Translation from English Idiom into Bahasa Indonesia in the subtitle of Spellbound Movie - Putri, Fenitra Mufti Rahma Budi Putri; Afifulloh, M. (Suara Bahasa, 2025)
Analysis of Idiom Translation from English Idiom into Bahasa Indonesia in the subtitle of Spellbound MovieFenitra Mufti Rahma Budi Putri1*, M. Afifulloh2Universitas Terbuka, Indonesia1Universitas Bangka Belitung, Indonesia2Fenitra64@gmail.com*Received: 10/06/2025 Revised: 11/07/2025 Accepted: 24/05/2025Copyright©2025 by authors. Authors agree that this article remains permanently open access under the terms of the Creative Commons Attribution License 4.0 International LicenseAbstrakIdiom merupakan kelompok kata tetap yang memiliki makna tertentu. Menerjemahkan idiom ke dalam bahasa lain dapat menjadi rumit dan menantang karena idiom tidak dapat diterjemahkan. Penelitian ini bertujuan untuk mengkaji idiom dalam bahasa Inggris dan penerjemahannya ke dalam bahasa Indonesia. Data yang digunakan dalam penelitian ini adalah idiom dari film “Spellbound”. Peneliti menggunakan metode analisis dokumen kualitatif (Morgan, 2022). Peneliti menemukan 22 idiom dalam film Spellbound. Penelitian ini menghasilkan idiom yang diterjemahkan menjadi idiom sebesar 2.72%, sedangkan yang diterjemahkan menjadi non-idiom sebesar 77.3%. Penelitian ini juga menemukan tiga strategi penerjemahan dari 8 yang digunakan untuk menerjemahkan idiom. Hasilnya adalah: penerjemahan dengan kata-kata yang lebih umum 45.5%, kata-kata netral/kurang ekspresif 31.8%, dan penerjemahan dengan parafrase 22.7%.Kata kunci: strategi penerjemahan; ekspresi idiomatik; penerjemahan idiom; film Spellbound.AbstractIdioms are fixed groups of words that have a specific meaning. Translating idioms into other languages can be complicated and challenging because idioms cannot be translated. This study aims to examine idioms in English and their translation into Indonesian. The data used in this study are idioms from the movie “Spellbound.” The researcher used a qualitative document analysis method (Morgan, 2022). The researcher found 22 idioms in the Spellbound movie. This study resulted in idioms translated into idioms of 22.7%, while those translated into non-idioms were 77.3%. This study also found three translation strategies from 8 used to translate idioms. The results are: translation with more common words 45.5%, neutral/less expressive words 31.8%, and translation with paraphrases 22.7%.